Neoproterozoic peritidal facies of the Villa Mónica Formation, Sierra La Juanita, Tandilia, Argentina - Manassero, Marcelo (2012)
From field observations and petrographic studies, a complex association of peritidal carbonate and siliciclastic facies have been recognized in the Villa Mónica Formation (Neoproterozoic), Sierra La Juanita, outcropping at the quarries of Estancia La Siempre Verde, Estancia La Placeres and Estancia Don Camilo, where carbonate facies have not been described ´in situ` since their discovery in 1967. Three different detailed stratigraphic sections are fully described. On the one hand, calcareous facies (well-preserved head stromatolites) have developed in a shallow subtidal to lower intertidal environment. Laminated microbial mats, with millimetric to centimetric scale siliciclastic intercalations, were deposited in low-energy intertidal conditions. Short-lived continental input of quartzose clastic sediments did not obliterate the microbial colonies, which grow following a pattern of thin cycles. On the other hand, heterolithic facies, developed in high-energy intertidal conditions towards the top of the succession illustrate progressive change in the paleoenvironmental conditions which evolved from a shallow prograding carbonate platform, with periodical sea level oscillations, to siliciclastic tidal influenced littoral conditions with minor development of microbial mat deposits. The recognition of ‛MISS’(microbially induced sedimentary structures) represented by microbial mats developed in siliciclastic facies was decisive for the evaluation of paleoenvironmental conditions and for the decision to assign heterolithic lithofacies described in this paper to the Villa Mónica Formation. These microscopical structures suggest and alternation of organic microbial activity with tractive and suspensive events. The coast line was probably oriented N-S with the deeper facies located to the west. A paleoenvironmental model is proposed for the area.